Learnerships in South Africa : the role of workplace adjustment as a mediator between social support and learner performance and satifaction - Blandin De Chalain, Megan Maire (Department of Psychology, 2015)
The South African economy is hindered by high unemployment, partly due to a lack of required skills in the country. Learnership programmes were implemented to contribute to skills development however there is limited research into the scope, magnitude and outcomes of these programmes. Previous research into learnerships has highlighted the importance of building support structures into these programmes in order to ensure their effectiveness. This study considered the role that workplace adjustment (self-efficacy, role clarity and social acceptance) has on the relationship between social support (co-workers, family, supervisors and mentors) and job satisfaction and self-perceived performance. Results indicated that coworker, supervisor and mentor support are related to performance via their link with workplace adjustment and that family support is related to job satisfaction via its link with workplace adjustment. This research aimed to create awareness about the internal processes and benefits of support personnel within South African learnerships. The results revealed that the quality rather than the number of support sources provided is important. Positive perceptions of support from co-workers, family, supervisors and/ or mentors was related to higher levels of job satisfaction and self-perceived performance. Additionally, learners who perceived the quality of support offered as high were more adjusted to the workplace. The study may not provide an accurate representation of learnerships in South Africa as a result of limitations such as the use of a self-reporting performance measure. Future research may elicit more accurate and representative analysis through the use of interviews or more objective measures when collecting data.